ANTIOXIDANT ACTIVITY OF SOME NEWLY PREPARED SYMMETRICALLY AZO DYES DERIVED FROM SULFA DRUGS - MUHAMMAD‑ALI, MUNTHER ABDULJALEEL; HAMZA SALMAN, HUSSAM; JASIM, EKHLASQANBER (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Sulfa drugs (sulfonamides) were the first type of drugs largely medically used for preventive and chemotherapeutic agents against various types of diseases. To the date, much research has been directed toward the synthesis sulfa drug derivatives such as azo‑sulfa drug compounds. The aim of the present study is to synthesize of azo‑sulfa compounds as antioxidant agents. Methods: First, three of sulfa drugs react with 4‑methoxy‑1,2‑Naphthoquinone in aqueous medium by stirring at room temperature to give symmetrically azo‑sulfa compounds. The colored compounds which formed were examined their structures by infrared and proton nuclear magnetic resonance spectral techniques. Results: Three symmetrically azo‑sulfa compounds were tested as antioxidant agents compared with ascorbic acid (AA) using 2,2‑diphenyl‑1‑picrylhydrazyl method. The results indicated that these compounds had good activities (57.79–73.69%) at 30 μg/ml, which had less activity than AA (81.34%) at the same concentration. These results referred the IC50 which had values (15.23–21.35 μg/ml), whereas AA had 7.59 μg/ml. Conclusion: Attachment of heterocyclic rings containing nitrogen and oxygen (isoxazole) on the azo‑sulfa compounds can enhance the antioxidant activity as compared with the heterocyclic rings containing nitrogen only (pyrimidine) and without heterocyclic rings, which enhanced the lipophilicity which may increase the bioavailability and efficacy of the drug.